Implementation of a City-Level Digital Education Strategy Through School-Level Development Projects During the COVID-19 Pandemic - Reinius, Hanna; Korhonen, Tiina; Tiippana, Netta; Laine, Tea; Elina, Elina Hannula; Juuti, Kalle; Hakkarainen, Kai; Lavonen, Jari (The international journal of educational organization and leadership, 2025)
This study aimed to investigate the effects of city-level digital education strategy and its implementation on promoting innovative digital educational practices through school-level development projects during the COVID-19 pandemic. The research examined the achievements of the city-level digital education strategy in relation to teachers’ digital competencies through self-assessment questionnaires and interviews with teachers. The questionnaire measured teachers’ generic digital competence, digipedagogical competence and professional digital competence at the beginning and end of the development projects, while the interviews explored teachers’ perceptions of the support provided by co-development projects for the adoption of the digital education strategy. An exploratory factor analysis was conducted, and the means of the pre- and post-tests were compared. The results showed that although teachers’ digital competencies generally remained at a satisfactory level, the functional use of digital tools was improved. This result was supported by the interview analyses, with teachers emphasizing the significance of support for integrating innovative ideas and knowledge into classroom practices. The findings suggest that it is essential to encourage teachers’ active participation and collaboration in digipedagogical development initiatives while simultaneously contextualizing the activities to suit the specific needs of individual classrooms and teacher communities to achieve genuine progress in implementation.